PERAN SENI HADRAH DALAM MENCEGAH KENAKALAN REMAJA DI MAJELIS SHOLAWAT NURUL IMAN - Mafzal Mafzal; Syamsul Arifin; Azhar Azhar (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
ABSTRACT Adolescents’ vulnerability to negative peer influences does not always stem from a tendency to violate social norms; it may also arise from limited access to social spaces that provide acceptance, meaningful activities, and a sense of direction. The Nurul Iman Sholawat Assembly in Kekalik Manggis offers hadrah as a communal setting where religious practice, artistic expression, and youth interaction converge. This study examines the role of hadrah in preventing juvenile delinquency while identifying conditions that support or constrain its sustainability. A qualitative case-study design was employed. Data were gathered through activity observations, in-depth interviews with one assembly leader and five adolescent members, and documentation of group schedules and activities. The data were examined through sorting, thematic categorization, narrative presentation, and gradual interpretation. Participation in rehearsals, sholawat, maulid, dhikr, religious sermons, and event preparation fostered religious habits, discipline, responsibility, and more supportive peer relationships. Viewed through Travis Hirschi’s Social Control Theory, these processes strengthened attachment, commitment, involvement, and belief as social bonds that shaped adolescents’ behavioral choices. Family support, mentors, community acceptance, and members’ enthusiasm sustained the activities, whereas scheduling conflicts, limited facilities, external environmental influences, and social media distractions posed challenges. Hadrah can therefore be positioned as a participatory form of community social control and a culturally grounded preventive strategy for youth development. ABSTRAK Kerentanan remaja terhadap pergaulan negatif tidak selalu berawal dari kecenderungan melanggar norma, tetapi juga dari terbatasnya ruang sosial yang memberi penerimaan, arah aktivitas, dan pengalaman bernilai. Majelis Sholawat Nurul Iman Kekalik Manggis menghadirkan seni hadrah sebagai ruang perjumpaan antara praktik religius, ekspresi seni, dan kebersamaan remaja. Kajian ini menelaah peran hadrah dalam mencegah kenakalan remaja sekaligus memetakan kondisi yang menopang maupun membatasi keberlangsungannya. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui observasi kegiatan, wawancara mendalam terhadap satu ketua majelis dan lima anggota remaja, serta dokumentasi agenda dan aktivitas kelompok. Seluruh data ditelaah melalui proses pemilahan, pengelompokan tema, penyajian naratif, dan penarikan makna secara bertahap. Keterlibatan dalam latihan, sholawat, maulid, dzikir, tausiyah, serta persiapan kegiatan membentuk kebiasaan religius, kedisiplinan, tanggung jawab, dan relasi pertemanan yang lebih suportif. Dalam kerangka Social Control Theory Travis Hirschi, proses tersebut menguatkan attachment, commitment, involvement, dan belief sebagai ikatan sosial yang mengarahkan pilihan perilaku remaja. Dukungan keluarga, pembina, masyarakat, dan antusiasme anggota memperkuat kegiatan, sedangkan benturan jadwal, keterbatasan sarana, pengaruh lingkungan luar, dan media sosial menjadi hambatan. Hadrah dapat diposisikan sebagai kontrol sosial komunitas yang partisipatif dan alternatif preventif berbasis budaya lokal.